The ontogeny-specific thermal sensitivity of the seagrass Posidonia oceanica - Rinaldi, Alessandro; Martinez, Marco; Badalamenti, Fabio; D’Anna, Giovanni; Mirto, Simone; Marín-Guirao, Lazaro; Procaccini, Gabriele; Montalto, Valeria (Frontiers in Marine Science, 2023)
The rapid increase in sea-water temperatures and frequency of extreme thermal events have amplified the risk of functional extinction of Mediterranean species such as the endemic long-lived seagrass Posidonia oceanica. Because of the valuable ecological functions and ecosystem services the species provides, understanding the life-stage specific thermal vulnerability is crucial to accurately predict the consequences of current and future global climate change and to protect and conserve existing meadows. To this end, here we report a study on the ontogeny-specific thermal sensitivity of important physiological functions (i.e. respiration and net production) of three different early life history stages of P. oceanica, namely seed, seedling (4-month-old individuals) and 16-month-old plantlet by measuring thermal performance curves (eleven temperatures treatments between 15-36ºC with n=8). All three stages examined showed photosynthetic activity during light exposure with similar optimal temperatures for both net and gross production. Gross photosynthesis increased with rising temperature up to 28-30°C, subsequently declining at higher temperatures until complete inhibition at 36°C. The metabolic response of seeds was found to be temperature-dependent up to 26°C, while respiration of seedlings and plantlets was almost stable up to 28-30°C, but increased markedly at higher temperatures, resulting in a negative whole-plant C balance at temperatures above 32°C. Overall, our results show that seedlings and plantlets tolerate a wider temperature range (15 -32°C) than seeds, which experience metabolic and physiological dysfunction from 26-28°C onwards. These findings suggest that the impact of warming on recruitment in P. oceanica meadows may vary depending on the timing of marine heatwaves (i.e. mid-spring to mid-autumn) and provide useful knowledge to inform restoration programs using early life stages of the species. In conclusion, the study of physiological responses during the early life stages of species is key to identify life history stages that are particularly vulnerable to climate change, which is vital knowledge for ecosystem management and conservation.